Design of a trichogramma balls UAV delivery system and quality analysis of delivery operation - Xing, Hang; Li, Mengjie; Qin, Yijuan; Fan, Gangao; Zhao, Yinwei; Lv, Jia; Li, Jiyu (Frontiers in Plant Science, 2023)
The field boundaries in our country are complex. In attempts to control pests via trichogramma-dominated biological control, the long-term practice of manual trichogramma release has resulted in low control efficiency, thereby impeding sustainable agricultural development. Currently, the novel approach involves utilizing Unmanned Aerial Vehicles (UAVs) for trichogramma balls delivery; however, the system is still in its nascent stages, presenting opportunities for enhancement in terms of stability and accuracy. Furthermore, there is a notable absence of comprehensive operational quality assessment standards. In this study, we establish a stable and accurate trichogramma balls delivery system using a four-axis plant protection UAV and introduce a comprehensive evaluation method for trichogramma balls delivery system. When dealing with fields with complex boundaries, it is beneficial to divide them into rectangular, trapezoidal, and stepped small fields at the boundary and perform operations within these small fields. According to our proposed evaluation method, when only considering the effect of field operations, the most effective boundary division shape is trapezoidal, followed by rectangular. and the worst is stepped. If both field operation effectiveness and the utilization effect of placed trichogramma balls are considered, the optimal shape is trapezoidal, then stepped, with rectangular being the least effective. Consequently, for UAV sub-area operations in complex boundary fields, it is advisable to divide the boundaries into trapezoids wherever possible. Field experiment results indicate that the system’s delivery area can reach up to 4158 m²/min and the coverage rate of released trichogramma balls can exceed 97%. The system design methodology and comprehensive operational quality evaluation method proposed in this article provide technical support and scientific basis for the application and promotion of UAV delivery trichogramma balls system. This is conducive to the high-quality development of agriculture.